Entomofauna associada à cultura da melancia no semiárido do Rio Grande do Norte - Costa, Ewerton Marinho da (2012)
Watermelon (Citrullus lanatus (Thumb) Matsum. & Nakai) is one of the main cucurbits cultivated in Brazil, and the Northeast region the country's the largest producer. In the state of Rio Grande do Norte, the third largest producer of watermelon from the northeast, the cultivation of this vegetable is an activity expanding, especially in the farming area Assu-Mossoró. Despite the expansion and technification the cultivation this cucurbit cultivation on RN, the lack of information about the insect community associated with the culture still represents a major barrier in pest management. Thus, the aim of this study was to survey the insect fauna associated with the watermelon crop in the municipality of Baraúna, RN. The insect fauna survey was conducted in an area of commercial production of watermelon. The catch of insects was carried out weekly during the crop cycle using three types of traps, Pitfall, Moericke (adapted) and McPhail, in density 20, 20:01 traps per hectare, respectively. Were collected a total of 14,460 insects, belonging to eight orders: Coleoptera, Hymenoptera, Hemiptera, Orthoptera, Dermaptera, Diptera, Thysanoptera and Lepidoptera, and distributed in 64 families. Orders Diptera, Coleoptera and Hymenoptera contributed the largest number of specimens, presenting the relative frequencies of total 37.88%, 26.83% and 21.60% respectively. We collected 24 families of Hymenoptera, 12 of Coleoptera, 16 of Diptera , 7 of Hemiptera and 2 of of orthopteros. The orders Dermaptera, Thysanoptera and Lepidoptera were represented by one family each. Was observed in the presence in field leafminer (Diptera: Agromyzidae) and whitefly (Hemiptera: Aleyrodidae). The natural enemies insect fauna (predators and parasitoids) associated with the watermelon crop was diversified and abundant. It was found in the region the occurrence of pests of watermelon and the presence of insects with the potential to become pests in this crop